Budaya dalam Adaptasi Komunikasi Bisnis Global Penggemar K-Pop melalui Media Sosial - Bachtiar, Mahdawanti Dian; Sevilla, Pavita; Nurfauziah, Puja Kharisma; Triwardhani, Ike Junita (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
One exciting innovation relevant to the research context is the current K-Pop phenomenon that has penetrated the field of intercultural business communication and involves transactions from two or more countries. Because of that, this research aims to find out how intercultural business communication occurs in the context of global business among K-Pop fans. The informant in this study is one of the K-Pop merchandise warehouse service providers in Indonesia. This research is qualitative research with a case study method. Data collection methods were obtained through interviews with informants. The results of this study show the importance of culture in business communication adaptation to overcome cultural differences in global business and also admit the challenges faced, such as language differences, business norms, and technological barriers